Development Impact of the Kaldera Park Toba Nomadic Escape Destination on Tourists' Revisit Intention - Manalu, Triana; Ornando Simorangkir, Cavin; Ali Sukran, Muhammad; Sartika Purba, Dewi; Ramadhan, Givano (JMET: Journal of Management Entrepreneurship and Tourism, 2024)
The growing interest in tourism opens up opportunities for developing tourism as a recreational industry and an economic circulation opportunity. The Kaldera Toba Nomadic Escape, a tourism destination development initiative by Indonesian government, is envisioned as a world-class recreational industry combining natural attractions, Batak culture, and artificial features. This study delves into the intention to revisit and the components influencing tourists' interest. The research uses SMART PLS to analyze survey data collected from tourists. The findings indicate the attraction component is the main reason tourists return. Although accessibility and amenities are essential, they do not receive much attention from tourists and must focus more on needs, changing trends, and tourist demands.